Extraction, purification and characterization of antifungal and antibacterial substances produced from Bacillus velezensis CP 1604 - Trung, Trịnh Thành; Vân, Đinh Thị Tuyết; Liên, Nguyễn Phương; Lương, Đào Thị; Hợp, Dương Văn (Vietnam Journal of Biotechnology, 2016)
Bacillus velezensis is one of the members of the Bacillus subtilis species complex which is generally considered as safety organism. The bacterium possesses several beneficial properties for crops, especially production of antifungal and antibacterial agents against plant pathogens. In this study, we aimed to investigate the biological properties of antimicrobial subtances produced from B. velezensis CP 1604. From liquid culture, substances with activity against Fusarium oxysporum and Xanthomonas oryzae were extracted by means of adsorption with Amberlite XAD-7, extraction from lyophilized powder using ethanol, precipitation at low pH and extraction with organic solvents of 1-butanol and 2-pentanol. The substances were subsequently purified using High Performance Liquid Chromatography (HPLC). Antifungal substance was eluted at 5.328 min while antibacterial substance was observed at 15.313 min. Mass spectrometry analysis showed that antifungal substance was iturin A with molecular weight of 1042 Da and antibacterial substance was macrolactin A with molecular weight of 402 Da. The antifungal substance was stable at high temperature but antibacterial activity was significantly reduced when treated at 100° C for 2 hours. Both substances reduced the activity at low pH but the activities still maintained at high pH. The antimicrobial activities against the fungal and bacterium were not affected when treated with hydrolytic enzymes such as trypsin, α-chymotrypsin, amylase, lipase and proteinase K. Further safety and efficiency investigations of the antifungal and antibacterial substances from B. velezensis CP 1604 on the plant disease control are required in order to seek for the potential application on sustainable agricultural production